Impact of time between thrombolysis and endovascular thrombectomy on outcomes in patients with acute ischaemic stroke - Wagner, Lora; Mohrbach, Desiree; Ebinger, Martin; Endres, Matthias; Nolte, Christian H.; Harmel, Peter; Audebert, Heinrich J.; Rohmann, Jessica L.; Siegerink, Bob (Frontiers in Neurology, 2022)
Background Benefits of endovascular thrombectomy (ET) after intravenous thrombolysis (IVT) for patients with acute ischaemic stroke (AIS) have been demonstrated, but analyses of the relationship between IVT-ET time delay and functional outcomes among patients receiving both treatments are lacking. Methods We used data from the “Berlin—Specific Acute Treatment in Ischaemic and haemorrhAgic stroke with Long-term outcome” (B–SPATIAL) registry. Between January 1st, 2016 and December 31st, 2019, we included patients who received both IVT and ET. The primary outcome was the 3-month ordinal modified Rankin scale (mRS) score. The IVT-ET time delay was analyzed in categories and continuously. We used adjusted ordinal logistic regression to estimate common odds ratios (cOR) and 95% confidence intervals (CI). Secondary analyses involved flexible modeling of IVT-ET delay and dichotomous outcomes. Results Of 11,049 patients, 714 who received IVT followed by ET were included. Compared with having an IVT-ET window >120 min (reference), for an IVT-ET window < 30 min, we obtained adjusted cORs for mRS of 0.41 (95% CI: 0.22 to 0.78); and 0.52 (95% CI: 0.33 to 0.82) for 30 to 120 min. Secondary analyses also found protective effects of shorter time delays against “poor” functional outcomes at 3 months. Conclusions In patients with AIS, shorter IVT-ET intervals were associated with better 3-month functional outcomes. While the time-to-IVT and time-to-ET include the time until medical attention is received, the IVT-ET time delays fall entirely within the domain of medical management and thus might be easier to optimize.